Nucleated red blood cell count in term and preterm newborns: reference values at birth. Issue 2 (21st February 2005) - Perrone, S; Vezzosi, P; Longini, M; Marzocchi, B; Tanganelli, D; Testa, M; Santilli, T; Buonocore, G
Abstract : The prognostic value of nucleated red blood cell count at birth in relation to neonatal outcome has been established. However, reference values were needed to usefully interpret this variable. The normal range of reference values for absolute nucleated red blood cell count in 695 preterm and term newborns is reported.